Healthy myeloid-derived suppressor cells express the surface ectoenzyme Vanin-2 (VNN2). (February 2022) - Soler, David C.; Kerstetter-Fogle, Amber; Young, Andrew B.; Rayman, Pat; Finke, James H.; Debanne, Sarah M.; Cooper, Kevin D.; Barnholtz-Sloan, Jill; Sloan, Andrew E.; McCormick, Thomas S.
Highlights: Several novel surface proteins were identified in monocytic MDSC from healthy patients. Monocytic MDSC present in healthy patients express high levels of the surface VNN2 ectoenzyme. VNN2 levels decrease in monocytic MDSC present in high-grade glioma patients. VNN2 might work as a circuit breaker to rein in monocytic MDSC immunosuppressive functions. Abstract: Study of human monocytic Myeloid-Derived Suppressor cells Mo-MDSC (CD14 + HLA-DR neg/low ) has been hampered by the lack of positive cell-surface markers. In order to identify positive markers for Mo-MDSC, we performed microarray analysis comparing Mo-MDSC cells from healthy subjects versus CD14 + HLA-DR high monocytes. We have identified the surface ectoenzyme Vanin-2(VNN2) protein as a novel biomarker highly-enriched in healthy subjects Mo-MDSC. Indeed, healthy subjects Mo-MDSC cells expressed 68 % VNN2, whereas only 9% VNN2 expression was observed on CD14 + HLA-DR high cells (n = 4 p < 0.01). The top 10 percent positive VNN2 monocytes expressed CD33 and CD11b while being negative for HLA-DR, CD3, CD15, CD19 and CD56, consistent with a Mo-MDSC phenotype. CD14 + VNN2 high monocytes were able to inhibit CD8 T cell proliferation comparably to traditional Mo-MDSC at 51 % and 48 % respectively. However, VNN2 expression on CD14 + monocytes from glioma patients was inversely correlated to their grade. CD14 + VNN2 high monocytes thus appear to mark a monocytic population similar to Mo-MDSC only in healthy subjects, which may be useful for tumor diagnoses.